2022
DOI: 10.3390/brainsci12030305
|View full text |Cite
|
Sign up to set email alerts
|

Functional Coupling of the Locus Coeruleus Is Linked to Successful Cognitive Control

Abstract: The locus coeruleus (LC) is a brainstem structure that sends widespread efferent projections throughout the mammalian brain. The LC constitutes the major source of noradrenaline (NE), a modulatory neurotransmitter that is crucial for fundamental brain functions such as arousal, attention, and cognitive control. This role of the LC-NE is traditionally not believed to reflect functional influences on the frontoparietal network or the striatum, but recent advances in chemogenetic manipulations of the rodent brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 119 publications
(209 reference statements)
1
12
0
Order By: Relevance
“…1C. Pupillometry as a non-invasive measure of LC activation Non-luminance mediated changes in pupil size are relatively easy to measure non-invasively and have been found to covary with a range of behavioral, cognitive and autonomic factors and with neural activity in many parts of the brain including some of the major neuromodulatory systems [Jepma and Nieuwenhuis, 2011 Grueschow et al, 2022]. For this review, I will focus on relationships between changes in pupil size and activation of the LC-NE system.…”
Section: B Inputs To the Locus Coeruleusmentioning
confidence: 99%
“…1C. Pupillometry as a non-invasive measure of LC activation Non-luminance mediated changes in pupil size are relatively easy to measure non-invasively and have been found to covary with a range of behavioral, cognitive and autonomic factors and with neural activity in many parts of the brain including some of the major neuromodulatory systems [Jepma and Nieuwenhuis, 2011 Grueschow et al, 2022]. For this review, I will focus on relationships between changes in pupil size and activation of the LC-NE system.…”
Section: B Inputs To the Locus Coeruleusmentioning
confidence: 99%
“…Using an emotional face-word Stroop task (Etkin et al, 2006), it has been demonstrated that the LC-NE system is involved in emotional conflict resolution (Grueschow et al, 2022), and more importantly, pupillary responses in this task have been linked to the LC-NE system (Grueschow et al, 2020(Grueschow et al, , 2021, revealing larger task-evoked pupil dilation in the incongruent condition compared to the congruent condition. Consistent with previous research (Grueschow et al, 2020(Grueschow et al, , 2021, we replicated these findings in a cohort of Asian participants using culturally distinct face-word stimuli, showing larger pupil dilation in the incongruent condition compared to the congruent condition.…”
Section: Linking the Lc-ne System To Task-evoked Pupil Dilationmentioning
confidence: 99%
“…It is also important to note that the LC-NE system interconnects with various areas of the brain in the context of pupil modulations (Joshi & Gold, 2020;Strauch et al, 2022). For instance, recent evidence suggests that the functional coupling between the LC-NE system and frontoparietal regions is crucial in predicting individual differences in cognitive control during an emotional face-word Stroop task (Grueschow et al, 2020(Grueschow et al, , 2021(Grueschow et al, , 2022. These together suggest that caution should be exercised when interpreting changes in pupil size at constant luminance as an exclusive measure of the activity of the LC-NE system, and considerations on the complex relationship between pupillary responses and the LC-NE system under different task conditions are needed to examine the LC-P3 hypothesis.…”
Section: Linking the Lc-ne System To Task-evoked Pupil Dilationmentioning
confidence: 99%
See 2 more Smart Citations